Odpowiedzi

Najlepsza Odpowiedź!
2010-01-12T10:02:57+01:00
2y-5x 7-8y
______+__________= 0
6 3
3x-y=-2
-y=-2-3x
y=2+3x

[2(2+3x)-5x]/6+[7-8(2+3x)]/3=0
(4+6x-5x)/6+(7-16-24x)/3=0 obie strony mnozymy przez 6
4+x-18-48x=0
-47x=14
x=-14/47

y=2+3x
y=2+3(-14/47)
y=1 i 5/47

chyba że tam w pierwszym równaniu brakuje x przy 7
2y-5x 7x-8y
______+__________= 0
6 3
3x-y=-2
-y=-2-3x
y=2+3x

[2(2+3x)-5x]/6+[7-8(2+3x)]/3=0
(4+6x-5x)/6+(7x-16-24x)/3=0 obie strony mnozymy przez 6
4+x-16-17x=0
-16x=-12
x=12/16=3/4

y=2+3x
y=2+3*3/4
y=4 i 1/4